Effects of public health restrictions during the pandemic on Kuwait’s equity market: An ARDL bounds testing approach - Al-Alawnh, Noor Aldeen Kassem; AL-Radaideh, Ibrahim Saleh; Hani, Laith Yousef Bani; Alawamreh, Mohammad Ismail Sulieman; Thaer, Abutaber (Asian Journal of Economic Modelling, 2026)
The objective of this study was to examine the effects of public health restrictions during the pandemic on the equity market in Kuwait by employing daily data collected over the period from January 23, 2020, to December 31, 2021. The study used the Autoregressive Distributed Lag (ARDL) model to evidence cointegration between the Kuwaiti equity market and public health restrictions (NPIs). The findings indicate that the long-term adverse impact of public health restrictions such as school closures, stay-at-home orders, and travel bans has resulted in worsening market performance. Conversely, the equity market reacts positively to restrictions on gatherings. The study also found a positive association between the S&P 500 and the Kuwaiti equity market, implying that the S&P 500 positively impacts the Kuwaiti market. This research contributes to understanding market behaviors and offers strategic insights for risk mitigation and market resilience during future crises. Future research could incorporate sentiment measures, nonlinear ARDL methods, or comparative studies across GCC financial markets to deepen understanding of policy–market interactions during systemic shocks. Expanding on this study enhances understanding of the impact of public health restrictions on emerging country financial markets under pandemic conditions, providing valuable insights for policymakers and investors in future crises.